The rise of early modern science : Islam, China, and the West - Huff, Toby E., 1942- (2017)
The Rise of Early Modern Science argues that to understand why modern science arose in the West it is essential to study not only the technical aspects of scientific thought but also the religious, legal and institutional arrangements that either opened the doors for inquiry, or restricted scientific investigations. Toby E. Huff explores how the newly invented universities of the twelfth and thirteenth centuries, and the European legal revolution, created a neutral space that gave birth to the scientific revolution. Including expanded comparative analysis of the European, Islamic and Chinese legal systems, Huff now responds to the debates of the last decade to explain why the Western world was set apart from other civilizations
Introduction -- The comparative study of science -- Arabic science and the Islamic world -- Philosophy, science, and civilizational configurations -- The European legal revolution -- Madrasas and the transmitted sciences -- Universities and the institutionalization of science -- Science and civilization in China -- Education, examinations, and neo-Confucianism -- Appendix 1 : anatomy, and post-mortems in China -- Poverties and triumphs of Chinese science -- Appendix 2 : books and essays on western science and astronomy translated into Chinese by the Jesuits -- The rise of modern science -- Epilogue : science, history, and development
Includes bibliographical references (pages 334-375) and index
Keywords: Science -- Arab countries -- History; Science -- Islamic countries -- History; Science -- China -- History; Science -- Europe -- History